Fungos associados ao trato digestório de Phylloicus SPP. (Trichoptera: calamoceratidae) em riachos de baixa ordem na Amazônia brasileira - Santos, Taides Tavares dos (Universidade Federal do Tocantins, 2019)
The study of the digestive tract (DT) of insects as a habitat for fungal organisms represents an opportunity for understanding the symbiotic relationships between these organisms. In addition, it represents a hotspot for obtaining new fungal lineages with different potentials of biotechnological application. The objectives of the present work were to evaluate the occurrence, diversity and cellulolytic activity of filamentous fungi and of yeasts associated with the DT of Phylloicus (Trichoptera: Calamoceratidae), in streams of the Legal Amazon, under different ecological landscapes, in Brazil. Phylloicus larvae were collected in the streams of the Roraima, Pará and Tocantins states (n = 137) for the isolation of filamentous fungi, and in the Mato Grosso and Pará states (n = 113) for the isolation of yeasts. The filamentous fungi associated to three species of Phylloicus (P. amazonas, P. elektoros and P. fenestratus), as well as associated with Phylloicus spp., were subjected to solid-media screening for cellulolytic activity and identified by combining classical taxonomy and molecular [sequencing of internal transcribed spacer (ITS) regions of the rDNA]. Yeasts were also screened for cellulase production and were identified based on sequence analysis of the D1/D2 domains of the large subunit of rDNA. Filamentous fungi (n = 16) that presented the highest enzymatic indices in the solid medium screening were evaluated for cellulase production [total cellulase (FPAse); endoglucanase (CMCase) and cellobiohydrolases (avicellase)] by means of solid-state fermentation (SSF) using an agroindustrial residue (wheat bran) as a substrate. Among the results of this study, it was found that filamentous fungi are much more frequent in association with Phylloicus, occurring in 94.9% of the DT sampled, than yeasts, which occurred in only 31.0% of the sampled DTs. A total of 33 filamentous fungi taxa were obtained. The genus Penicillium was the most frequent (18.75%), followed by Pestalotiopsis and Trichoderma (10.42%, each). The occurrence of filamentous fungi taxa among host insect species varied widely, with more than half of the taxa unique to a particular host species. With respect to yeasts, a total of 20 species were obtained in association with Phylloicus spp. The most frequent genera were Candida, Papiliotrema, Rhodotorula (19.3% each) and Issatchenkia (15.8%). Regarding the cellulolytic activity of filamentous fungi, 45.6% (n = 62) of the strains tested showed cellulolytic activity. Among those with higher enzymatic indexes, six produced cellulase in one of three trials (FPAse, CMCase and avicellase). It was concluded that mycotic composition associated with Phylloicus DT is variable among host species. Cellulolytic activity is a restricted feature among the yeasts tested, whereas a significant portion of the filamentous fungi exhibits this characteristic activity, corroborating the possibility of this being a possible role played by these microorganisms in the interaction interface with their hosts. The species Cladosporium perangustum presents potential for application in biotechnological processes involving the production of cellulases.